Dual Hysteresis Model of MR Dampers - Gołdasz, Janusz; Sapiński, Bogdan; Jastrzębski, Łukasz; Kubik, Michal (Frontiers in Materials, 2020)
This study concerns modeling the hysteretic behaviour of magnetorheological (MR) dampers. In general, hysteresis is one of key factors influencing the output of such actuators. So far more attention of various researchers has been paid to studying the combined hysteretic behaviour of MR actuators by observing the relationships between the output (force/torque) and the inputs (current, velocity, position). However, these devices feature two distinct hysteretic mechanisms: mechanical/hydraulic and magnetic. The mechanical hysteresis is of different nature than the magnetic hysteresis due to the properties of ferromagnetic materials forming the actuator's elec- tromagnet circuit, and these should be split in the modeling process. In the present study we separate the magnetic hysteresis from the mechanical/hydraulic one by investigating the magnetic flux vs exciting current relationship of a commercial flow-mode MR damper subjected to sinusoidal current loading and independently of the mechanical excitations. The resulting behaviour of the electromagnetic circuit is then examined using the nonlinear inductor approach with hysteresis. Total hysteresis is then modeled using a non-linear inductor model in combination with a phenomenological parametric Maxwell type model of the damper.